REGRESSIVE ANALYSIS OF BRAKING EFFICIENCY OF M1 CATEGORY VEHICLES WITH ANTI-BLOCKING BRAKE SYSTEM - Sarayev, О.; Сараєв, А. В.; Сараєв, О. В. (Харьковский национальный автомобильно-дорожный университет, 2015)
The problematics of assessing the effectiveness of vehicle braking after road accidentoccurrence is considered. For the first time in relation to the modern models of vehicles equipped with anti-lock brakes there were obtained regression models describing the relationship between the coefficient of traction and a random variable of steady deceleration. This does not contradict the essence of the stochastic physical object, which is the process of vehicle braking, unlike the previously adopted method of formalizing this process, using a deterministic function.
РЕГРЕСІЙНИЙ АНАЛІЗ ЕФЕКТИВНОСТІ ГАЛЬМУВАННЯ АВТОМОБІЛІВ КАТЕГОРІЇ М1 З АНТИБЛОКУВАЛЬНОЮ СИСТЕМОЮ ГАЛЬМ
РЕГРЕССИОННЫЙ АНАЛИЗ ЭФФЕКТИВНОСТИ ТОРМОЖЕНИЯ АВТОМОБИЛЕЙ КАТЕГОРИИ М1 С АНТИБЛОКИРОВОЧНОЙ СИСТЕМОЙ ТОРМОЗОВ
Keywords: vehicle; road accident; braking; clutch; deceleration; calculation; автомобіль; аварія; гальмування; зчеплення; сповільнення; розрахунок; автомобиль; авария; торможение; сцепление; замедление; расчет; 656.081